2006
DOI: 10.1109/sibedm.2006.230968
|View full text |Cite
|
Sign up to set email alerts
|

Research the Acoustic Cloth Drying Process in Mock-Up of Drum-Type Washing Machine

Abstract: This article shows rewUlt of researches, aimed to increasing the efficiency and productiveness of "classic" cloth convective drying method in drumtype washing drying machine with simultaneous decreasing the power consumption by means of include the high-power acoustic radiator into washing machine design.Index Terns-ultrasonic devices, washing mashine, drying

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…As drum-type convective chambers are wide spread [2], we decided to conduct researches on the base of the construction simulating the working volume of such dryers.…”
Section: Theory Of Ultrasonic Dryingmentioning
confidence: 99%
“…As drum-type convective chambers are wide spread [2], we decided to conduct researches on the base of the construction simulating the working volume of such dryers.…”
Section: Theory Of Ultrasonic Dryingmentioning
confidence: 99%
“…Однако из-за негативного влияния на человека высоких уровней звукового давления и отсутствия эффективных акустических излучателей этот вид сушки не получил широкого промышленного распространения. В этой связи целесообразным является проведение исследований процесса сушки в безопасном для человека ультразвуковом диапазоне частот (более 20 кГц) [3].…”
unclassified
“…If the oscillation frequency is larger than 20 kHz, it generates ultrasonic waves that propagate through its surrounding media [12, 16]. Coming to the studies reported on ultrasonic cloth drying per se, to our knowledge, Khmelev et al [17,18] is the only paper on this topic. However, a non-contact technique was used in their study, making our study unique and the first of its kind.This study will address the feasibility of adopting the ultrasonic technique for cloth drying with the objective of achieving lower power consumption and process duration compared to the existing energy-intensive, thermal-based clothes dryers.…”
mentioning
confidence: 99%